PRODUCTION OF TURKISH NON-BRINED WHITE CHEESE FORTIFIED WITH VITAMIN D3 - Onaran, Bahar (Food and Feed Research, 2025)
Vitamin D deficiency is a prevalent issue, particularly in developing countries, and fortifying foods with vitamin D is an essential strategy to enhance public health. Enriching white cheese with vitamin D3 is an appealing option for consumers, especially for infants who require vitamin D supplementation. This study aimed to optimize the white cheese production process by directly adding commercial non-emulsified vitamin D3 oil to pasteurized milk and quantifying the resulting vitamin D3 content in the cheese. Traditional white cheese was produced to achieve a final concentration of 10 µg (400 IU) of vitamin D3. Using the HPLC-UV method, we compared the fortified cheese to a non-fortified control group regarding vitamin D3 content. Sensory analysis and microbiological analyses were also conducted. The study revealed that the fortified cheese contained 6.9 µg (276 IU)/100g of vitamin D3, with no statistically significant differences observed in sensory evaluation or microbiological safety between the two groups. Consequently, our findings suggest that vitamin D3-fortified cheeses can effectively contribute to meeting daily vitamin D requirements. This research highlights the potential for developing cheeses with specified vitamin D content and represents a significant advancement in functional food production, promoting public health.